2019
DOI: 10.1111/aas.13372
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the 90% effective dose of intranasal dexmedetomidine for sedation during electroencephalography in children

Abstract: EEG is a valuable diagnostic tool for children with epilepsy, delirium and other central nervous system lesions. Children likely experience difficulty falling asleep when they are scheduled to undergo EEG. Therefore, sedation is very important.Sedation for EEG in uncooperative children remains controversial because most anaesthetics and sedatives have some effect on brain waves. Many sedative medications, such as chloral hydrate, hydroxyzine and dexmedetomidine (DEX), have been used in children undergoing EEG.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
5
2
Order By: Relevance
“…Differently, with intranasal administration there isn't a standard dose, because of the heterogeneity of studies. The mean dose in our population (4.34 ± 0.87 mcg/kg) is higher than what reported in literature [22], maybe it depends on the age of patients included or on the higher number of unsuccessful procedures [15].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Differently, with intranasal administration there isn't a standard dose, because of the heterogeneity of studies. The mean dose in our population (4.34 ± 0.87 mcg/kg) is higher than what reported in literature [22], maybe it depends on the age of patients included or on the higher number of unsuccessful procedures [15].…”
Section: Discussioncontrasting
confidence: 62%
“…The offset in our study is included in the range described in literature (44-91 minutes) and it wasn't in uenced by the dose administered [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to be non-noxious to the nasal mucosa in different studies [24,25]. But in the present study, nasal discomfort was observed in 2 children with IND administration, which could be due to administration of the drug by a syringe and would have been best avoided with the use of a mucosal atomizer device [28], whereas a success rate of 87% was reported in a similar study using IND at a dose of 2.5 µg/kg [29]. In a recent systematic review, the success rate of IND was shown to vary from 30 to 100% depending on the dose of the drug and type of procedures requiring sedation [10].…”
Section: Discussioncontrasting
confidence: 54%
“…In our study, the success rate of the initial dose of 2.5 μg•kg − 1 DEX was 87.0% (3024/3475 cases). A recent study have found that 90% of the effective dose of intranasal DEX sedation was 3.28 μg•kg − 1 in children [23]. Another study found that the 50% effective dose and the 95% effective dose of intranasal DEX increased with increasing age in patients under 3 years of age [24].…”
Section: Discussionmentioning
confidence: 96%